PELATIHAN DAN PENDAMPINGAN PEMBUATAN PERANCAH INTERAKTIF BERBASIS WEB DAN PENERAPANNYA DALAM MODEL CONTEXTUAL TEACHING AND LEARNING DI SMP MUHAMMADIYAH 01 MEDAN - Azis, Zainal; Harahap, Tua Halomoan; Dachi, Surya Wisada (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The proposed partnership program is intended to solve two partner problems (SMP Muhammadiyah 01 Medan), namely: (1) lack of partner teacher skills in the design and implementation of online teaching where the learning structure is dominated by assignments, unavailability of scaffolding, and only a small part of the time. Meetings are used for explanations, and (2) teachers do not understand how to choose an appropriate learning model for the topic being taught. In the context of online learning, such difficulties will increase. The solutions offered to overcome the first problem are training in a web-based interactive scaffolding development workshop using Articulate Storyline 3 software, an online class development workshop using Google Classroom, and an online teaching design workshop including learning tools. The solution offered to overcome the second problem is assistance in applying web-based interactive scaffolding in the CTL model. The program implementation method refers to the Learn-Teach-Evaluate-Acknowledge method proposed by Buckenmeyer et al. (2013), which has been modified and agreed upon by the Proposing Team and partners to resolve specific problems faced by partners. The modifications made are: (1) Adding a Fostering phase (coaching) for the sustainability of activities; and (2) the adjustment of each phase to the principles of adult learning, as proposed by Alamdari et al. (2017), which focuses on experiential learning and self-motivation to encourage participants and instructors to participate actively.